2013
DOI: 10.1063/1.4803930
|View full text |Cite
|
Sign up to set email alerts
|

Energetic ion transport by microturbulence is insignificant in tokamaks

Abstract: Energetic ion transport due to microturbulence is investigated in magnetohydrodynamic-quiescent plasmas by way of neutral beam injection in the DIII-D tokamak [J. L. Luxon, Nucl. Fusion 42, 614 (2002)]. A range of on-axis and off-axis beam injection scenarios are employed to vary relevant parameters such as the character of the background microturbulence and the value of E b =T e , where E b is the energetic ion energy and T e the electron temperature. In all cases, it is found that any transport enhancement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 117 publications
2
22
1
Order By: Relevance
“…The distinction is not likely within the resolution of the experimental uncertainty. These simulations are not inconsistent with previous DIII-D experimental results which found that EP transport enhancement due to microturbulence to be below detectable levels and EP transport from coherent AE's considerably larger [17] and in the range of 1 m 2 s −1 . Figure 5 repeats the figure 4 panels using the beam-like slowing down NBI velocity distribution only and varying the beam-mix from on-axis to off-axis: 0.0, 0.22, 0.45, 1.00.…”
Section: Validation Of the Critical Gradient Modelsupporting
confidence: 71%
“…The distinction is not likely within the resolution of the experimental uncertainty. These simulations are not inconsistent with previous DIII-D experimental results which found that EP transport enhancement due to microturbulence to be below detectable levels and EP transport from coherent AE's considerably larger [17] and in the range of 1 m 2 s −1 . Figure 5 repeats the figure 4 panels using the beam-like slowing down NBI velocity distribution only and varying the beam-mix from on-axis to off-axis: 0.0, 0.22, 0.45, 1.00.…”
Section: Validation Of the Critical Gradient Modelsupporting
confidence: 71%
“…Plasmas 24, 122309 (2017) matches well the expected electrostatic diffusivity scaling for different values of g t . The lower-energy fast particles (E % 10T e0 ), which have been speculated to be most strongly affected by microturbulence, 44 have diffusivities one to two orders of magnitude less than seen for tokamak cases studied previously, 47 even despite the large gradients used. The inclusion of an external magnetic perturbation modeling tearing fluctuations violates assumptions on which the theory 22 is built.…”
Section: -8mentioning
confidence: 78%
“…The question whether microturbulence plays an important factor in fast particle-particularly beam ion-losses in tokamaks has not definitively been answered. [43][44][45][46] One approach in this area is to study decorrelation of fast particles from the microturbulence and calculate the resulting losses, 22,47 deriving scaling laws for diffusion as a function of particle energy. Notably, the assumptions made in these derivations hold in RFP geometry and should thus apply to MST fast ion diffusion at the radial locations where TEM or ITG microturbulence dominates.…”
Section: Energetic Particles In Mstmentioning
confidence: 99%
“…Moreover, the characteristic times associated with the individual fast-ion filaments (t ∼ 100 μs) in comparison with the fast-ion slowing-down time in these plasmas (τ s ∼ 100 ms) indicate that the phenomenon is likely to be collisionless. While turbulent mechanisms are found to be relevant for particle transport and acceleration in space and astrophysical plasmas, the effect of turbulence on fast ions is thought to be negligible in these experiments provided the large E=T e ratio (≥ 100) [28,29]. We therefore propose a resonant interaction between the beam-ion orbits and the parallel electric field emerging during the ELM, when magnetic reconnection is believed to take place [18].…”
mentioning
confidence: 82%